Сognitive-behavioral therapy in generalized anxiety disorder - Burda, Hanna (Psychosomatic Medicine and General Practice, 2017)
Generalized anxiety disorder - is a common disease, which is quite difficult diagnosed and treated. Cognitive-behavioral therapy is indicated to patients with GAD as a first-line method. This article provides an overview of the principles, advantages and evidence of the effectiveness of this type of therapy. Although cognitive behavioral therapy has advantage over other types of therapy for GAD, this issue requires further research, because there are problems such as a high percentage of patients interrupting therapy and relatively low percentage of clinically meaningful improvement.